Physico-chemical characteristics and effect on oxidative stress of red pitaya in swiss diabetic mice (Research, Society and Development, 2020)
Red pitaya (Hylocereus polyrhizus Weber Britton & Rose) is rich in antioxidants, which might help regulate oxidative stress, exacerbated in Diabetes Mellitus (DM). This study aimed to determine the centesimal composition, physicochemical characteristics and in vivo antioxidant effect of red pitaya in diabetic swiss mice. Pulp, seeds and peel were isolated and used for physicochemical and centesimal composition analysis. DM was induced in female Swiss mice through intraperitoneal Alloxan Monohydrate injection. Groups with 6 animals were formed: Healthy (SAUD), Untreated A and B (DNT A and DNT B), Metformin (MET), and groups fed with 20 (PIT20), 40 (PIT40), 200 (PIT200) and 400 (PIT400) mg of pulp with seeds extract/kg of animals’ body weight, by gavage, for 28 days. Thiobarbituric acid reactive species (TBARS) hepatic content was quantified by Malondialdehyde (MDA), to evaluate lipid peroxidation. Pitaya’s composition was similar to that previously reported. Pulp and peel showed insignificant lipid contents, expressive presence of carbohydrates, and fibers in all samples, especially peel. Lowest MDA was observed in PIT400, PIT200, and PIT40, compared to DNT A and B, and MET. Results were dose-dependent, suggesting pitaya consumption was associated with lower lipid peroxidation. Further studies on its composition and applications as a functional food are required, especially for humans and in DM.